Non-invasive imaging biomarkers of cellular injury and proliferation in nasopharyngeal carcinoma: insights from multiparametric MRI - Zhao, Changjiang; Xie, Lisi; He, Mengxi; Xiong, Xiong; Yu, Chengxin; Liu, Yang (Frontiers in Cell and Developmental Biology, 2025)
BackgroundEarly identification of therapeutic response and tumor proliferative status is essential in nasopharyngeal carcinoma (NPC). Multiparametric MRI-combining IVIM and DCE-provides quantitative biomarkers reflecting tissue diffusion, perfusion, and vascular permeability. We evaluated whether pre-treatment IVIM- and DCE-derived parameters predict short-term response to induction chemotherapy plus concurrent chemoradiotherapy and whether they correlate with tumor proliferation (Ki-67).MethodsIn this prospective study (n = 48; January 2021–January 2023), IVIM parameters (D, D*, f) and DCE parameters (Ktrans, Kep, Ve, Vp) were quantified before treatment. Treatment response at 6 months was classified by RECIST 1.1 as complete response (CR) or non-CR. Ki-67 index was determined by immunohistochemistry (cutoff 50%). Group comparisons used t-tests or Mann–Whitney U tests; logistic regression identified independent predictors; ROC analysis evaluated diagnostic performance; Spearman correlation tested associations with Ki-67.ResultsPre-treatment D was lower in the CR group (0.82 ± 0.12 vs. 0.92 ± 0.11 ×10-3 mm2/s; P = 0.007). Ktrans and Kep were higher in CR (0.95 ± 0.34 vs. 0.30 ± 0.31 min-1, P = 0.014; 0.16 ± 0.09 vs. 0.11 ± 0.06 min-1, P = 0.025). D was an independent predictor (P = 0.008). The combined model (D + Ktrans + Kep) yielded AUC = 0.834 (sensitivity 90.0%; specificity 61.4%). Ki-67 correlated negatively with D (r = −0.329, P = 0.022) and positively with Vp (r = 0.292, P = 0.044).ConclusionMultiparametric MRI can noninvasively predict short-term response and reflect proliferative status in NPC. Integrating IVIM-derived D with DCE-derived Ktrans and Kep improves early prediction of treatment efficacy; Vp may serve as an imaging surrogate for proliferation.